High-dose-rate brachytherapy in uterine cervix carcinoma: a comparison of dosimetry and clinical outcomes among three fractionation schedules - Wu, Haiyan; He, Yanan; Chen, Duke; Liu, Mei; Zhao, Xiujuan (Frontiers in Oncology, 2024)
Background: To assess the differences among three dose-fractionation schedules of image-guided adaptive brachytherapy (IGABT) in cervical squamous cell carcinoma (CSCC) by comparing the dosimetry and clinical outcomes. Methods: Forty-five patients with CSCC who underwent chemoradiotherapy and IGABT were retrospectively enrolled and divided into three groups based on their dose-fractionation schedules of brachytherapy as: Group-5.5 (5.5 Gy × 6 fractions), Group-6.0 (6.0 Gy × 5 fractions), and Group-7.0 (7.0 Gy × 4 fractions). The analyzed dose-volume histogram parameters included D90% and D98% of the high-risk clinical target volume (HR-CTV), D90% and D98% of intermediate-risk clinical target volume (IR-CTV), and D0.1cc and D2cc of the organs-at-risk (OARs, namely the bladder, rectum, sigmoid and small intestine). Furthermore, the therapeutic efficacy and late toxicities were also compared among the three groups. Results: The doses of HR-CTV and IR-CTV in Group-5.5 were found to be the highest among the three groups, followed by those in Group-6.0. Significant differences were found for the doses of HR-CTV between Group-5.5 and the other groups. There were no significant differences in the bladder, sigmoid and small intestine dose among the three groups. However, Group-6.0 yielded the lowest rectum received doses, with a significant difference in D0.1cc being detected between Group-6.0 and Group-5.5. The median follow-up time was 30.08 months [range, 6.57-46.3]. The numbers of patients with complete response in Group-5.5, Group-6.0 and Group-7.0 were 13, 14 and 14, respectively (P > 0.05). In regard to the toxicitiy, the incidence of radiation cystitis and proctitis in Group-6.0 was lower than that in Group-5.5 and Group-7.0 (P > 0.05). Conclusions: The dose-fractionation schedule of 6.0 Gy × 5 fractions provided the most beneficial effects with relatively low OARs doses, suggesting that this dose-fractionation schedule should be prioritized in the clinical application of brachytherapy in cervical cancer.